Comparison of AID users and non-users regarding glycemic control and diabetes distress: A mixed-methods study - Alexander Hadj-Abo; Burkhard Gusy; Monika Fleischhauer (PLoS ONE, 2026)
Aim This study compared glycemic control and diabetes distress in individuals with type 1 diabetes using automated insulin delivery (AID) systems versus those not using such systems, addressing a gap in research on psychosocial outcomes of diabetes technologies. Methods A sequential mixed-methods design was employed to examine differences between AID users and non-users. A total of 169 individuals with type 1 diabetes completed an online survey assessing HbA1c, total diabetes distress, and its subscales. Quantitative results were complemented by 12 follow-up interviews to provide contextual depth. Results The AID group (n = 80) showed significantly lower levels in HbA1c, total diabetes distress, and all subdimensions compared to the non-AID group (n = 89), which showed high CGM use (~94%). The largest effects emerged for Management Distress and Powerlessness . Interview data suggested that AID systems reduce the cognitive and emotional burden of diabetes self-management, which may explain these differences. Contrary to expectations, group differences in Hypoglycemia Distress and Negative Social Perception were smaller. This may be explained by the widespread use of continuous glucose monitoring (CGM) systems in the non-AID group, as participants from both groups reported CGM use to be helpful in reducing hypoglycemic events. Conclusions AID systems are associated with both, improved glycemic outcomes and enhanced psychosocial well-being. These findings underscore the multifaceted benefits of AID systems and highlight the importance of incorporating psychosocial dimensions into the evaluation of diabetes technologies. The mixed-methods approach proved valuable in capturing both quantitative and experiential aspects, providing a more nuanced understanding of patient experiences.